Utveckling av ett skogsbolags kontaktstrategi - Prejer, Björn (2005)
The supply of raw materials has always been an important issue in the Swedish Forest industry. Buying timber from local suppliers is important. To ensure raw materials to their industries the forest company must offer good prices and good business deals to their suppliers. The aims with this work are to find out how the contact between private suppliers of raw materials and how the forest company can be developed. To be able to do a complete study of the problems connecting with this subject a quality interview study has been done. Totally 12 suppliers of raw material was interviewed. Collection of data has been done with 12 different interviews. Just suppliers to one single forest company that are in this study, the suppliers deliver a minimum of 1000m3fub per year and all the suppliers are situated in the middle of Sweden. The basis of the interviews was a SWOT-analyze done together with some of my student colleagues at SLU. During the work with the interviews, a literature study was done in the subject Silviculture, interview work, business strategy and economy. The result shows that the form of business agreement between the supplier and the forest company works good. It is important that the business runs smooth and the quality of the thinning or other silvicultural methods is good. Some of the suppliers said that the local contact person from the forest company is more important than the actual company. The suppliers in this study are not sensitive to price fluctuations of pulpwood and timber. They do annual cuttings anyway. The buyer of the forest company has an important role in giving forestry advice to the suppliers, and it is mainly advise in forest and forest economy that the suppliers are interested in. The buyers need to improve their skills in forest economy to be able to give better advice. The suppliers don't feel that they have full control of the timber from their forest. The accounting of logs delivery must be better. Good knowledge about the decision situation of the private forest owner, and to give adapted advice to the forest owner, and the buyer can be more successive in his work.